2020
DOI: 10.1021/acs.analchem.9b05410
|View full text |Cite
|
Sign up to set email alerts
|

A Boric Acid-Functionalized Lanthanide Metal–Organic Framework as a Fluorescence “Turn-on” Probe for Selective Monitoring of Hg2+ and CH3Hg+

Abstract: Mercury detection remains an important task because of its high toxicity. Herein a new dual-signal probe based on a boric acid (BA)-functionalized lanthanide metal–organic framework (BA-Eu-MOF) was developed for the detection of Hg2+ and CH3Hg+ ions for the first time. The BA-Eu-MOF was synthesized by coordination of Eu3+ with 5-boronobezene-1, 3-dicarboxylic acid (5-bop) through a one-pot method. The 5-bop ligand not only acted as the “antenna” to sensitize the luminescence of Eu3+ but also provided reaction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
57
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(59 citation statements)
references
References 41 publications
2
57
0
Order By: Relevance
“…4,5 The ion-exchange reactions of MOFs have also been applied to various methods for the removal, separation, 6,7 and detection of metal ions. [8][9][10] Although in most cases, selectivity of the metal exchange reactions in MOFs exhibits a common trend as often observed in conventional ion-exchange systems, 11,12 unusual selectivity has been observed in ion-exchangeable MOFs. For example, Plabst et al 13 reported an exceptional selectivity for the ion-exchange reaction between alkali metal ions in an MOF comprising of 1,4-phenylenebis(methylidyne)tetrakis(phosphonic acid) (L; Fig.…”
mentioning
confidence: 87%
“…4,5 The ion-exchange reactions of MOFs have also been applied to various methods for the removal, separation, 6,7 and detection of metal ions. [8][9][10] Although in most cases, selectivity of the metal exchange reactions in MOFs exhibits a common trend as often observed in conventional ion-exchange systems, 11,12 unusual selectivity has been observed in ion-exchangeable MOFs. For example, Plabst et al 13 reported an exceptional selectivity for the ion-exchange reaction between alkali metal ions in an MOF comprising of 1,4-phenylenebis(methylidyne)tetrakis(phosphonic acid) (L; Fig.…”
mentioning
confidence: 87%
“…Moreover, the boric acid exhibits a strong affinity to fluoride ions, while its interaction with other anions is relatively weak, making it perfect for fluoride selective sensing. Reports on enhancing antenna effect resulted in "turn-on" sensing are rather few comparing to the "turn-off" mechanism discussed above (Karmakar et al, 2019;Fueyo-González et al, 2020;Min et al, 2020;Wang et al, 2020;Yue et al, 2020). However, it is obvious that "turn-on" sensors have advantages over the "turn-off" sensors, especially in the quantitative determination of an analyte in low concentration (Luo et al, 2020).…”
Section: Ratiometric Fluorescent Sensing Mechanismsmentioning
confidence: 99%
“…Over the past few years, lots of research groups tried to rapidly detect kinds of cations by the usage of NMOFs-based fluorescence sensors and have borne fruit [4]. In addition, many of them shared a similar sensing mechanism, in which NMOFs-based fluorescence sensors were selectively quenched by certain metal cations through the PET [93][94][95][96]. In this part, the latest and novel NMOFs sensors for cation detection will be introduced.…”
Section: Cationsmentioning
confidence: 99%